Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1590/s0073-47212011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the survival and growth of freshwater prawns Macrobrachium borellii and Palaemonetes argentinus (Crustacea, Palaemonidae)

Abstract: ABSTRACT. During the two-month rearing period, the effect of four water temperatures (15°C, 20°C, 25°C and 30°C) on survival rate, number of molts, and growth rate (molt increment and intermolt period) of juvenile Macrobrachium borellii Nobili, 1896 and Palaemonetes argentinus Nobili, 1901 prawns was evaluated in laboratory conditions. The two species showed some similarities in their both survival and growth pattern at different temperatures. The survival rate was highest at 20°C and 25°C, decreasing at the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This relatively short intermoult period can be related to the average temperature maintained in both studies; 20 ± 2°C (Díaz et al, 1998) and 23°C for the present study. Montagna (2011) reported for this species an optimum temperature of 25°C and detected an increased body size of P. argentinus in relation to a shorter intermoult. This rapid growth rate in optimum temperatures may be associated with increased food consumption (Wyban et al, 1995), which was widely available for the species under study.…”
Section: Post-moultmentioning
confidence: 74%
See 1 more Smart Citation
“…This relatively short intermoult period can be related to the average temperature maintained in both studies; 20 ± 2°C (Díaz et al, 1998) and 23°C for the present study. Montagna (2011) reported for this species an optimum temperature of 25°C and detected an increased body size of P. argentinus in relation to a shorter intermoult. This rapid growth rate in optimum temperatures may be associated with increased food consumption (Wyban et al, 1995), which was widely available for the species under study.…”
Section: Post-moultmentioning
confidence: 74%
“…Palaemon argentinus (Nobili, 1901), a freshwater shrimp that reaches a maximum size of 32 mm (females) and 29 mm (males) (Bond-Buckup and Buckup, 1989) can be maintained in the laboratory and offers a great variety of study opportunities, such as: reproductive biology (Schuldt and Capítulo, 1985), osmoregulation (Lignot et al, 1999;Ituarte et al, 2016), morphology, histology of the digestive tract (Sousa and Petriella, 2006), growth (Montagna, 2011), parasitism (Neves et al, 2004), moult cycle in the natural environment (Díaz et al, 1998;Felix and Petriella, 2003), behavioral ecology (Gancedo and Ituarte, 2017), and recently also the regulation of cell volume during the moult cycle (Foguesatto et al, 2017). Setogenesis in P. argentinus has been described only for juveniles (Díaz et al, 1998); some substages of the moult cycle of this species, however, have not yet been elucidated.…”
mentioning
confidence: 99%
“…Similarly, for M. borellii and P. argentinus. survival rate was reduced at temperatures of 15 and 30°C (Montagna, 2011). The growth of M. rosenbergii increased at 24-29°C, and decreased at 34°C (Habashy and Hassan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, Madlen (2010) showed that growth of M. rosenbergii declined in high temperature due to failure of enzymatic function. Therefore, as temperature is the most important limiting factor for metabolic functions in crustaceans, but particularly in shrimps directly determining metabolic rate and growth (Manush et al, 2004;Montagna, 2011;Crisp et al, 2017), it can change the energy flow (Montagna, 2011) and maybe food assimilation, affecting the weight and body condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation